Green synthesis of dimanganese trioxide nanoparticles using tamarind seed powder: Effect of tamarind seed powder concentration on the structural, electrical and electrochemical properties of dimanganese trioxide nanoparticles. (2022) - Premakumari, P.; Latha, H.K.E.; Nagaraju, G.
Abstract: In Rechargeable Battery, anode electrode plays a crucial role as it directly influences the electrochemical performance (High power and energy). This leads to synthesize a novel anode electrode material. Manganese oxide is one of the prominent transition metal oxides. Hence in the present work Dimanganese trioxide (Mn2O3) nanoparticles are synthesized using Green combustion synthesis process. Manganese (II) nitrate tetrahydrate is used as precursor and Tamarind seed powder is used as fuel in the synthesis process. Precursor weight is kept constant and fuel concentration is varied as 0.1 g, 0.2 g and 0.3 g. The precursor and fuel are mixed and calcinated at 700 °C to produce Mn2O3 nanoparticles. The Structural, Electrical and Electrochemical properties of the synthesized Mn2O3 nanoparticles are studied using XRD (X-ray diffraction), FTIR (Fourier Transform Infrared), SEM (Scanning Electron microscopy) and TEM (Transmission Electron Microscopy), UVDRS (Ultraviolet Differential Reflectance Spectroscopy), EIS (Electrochemical Impedance Spectroscopy) and BET (Brunauer-Emmett-Teller). XRD result confirms that the synthesized Mn2O3 nanoparticles are highly crystalline with cubic structure. The FTIR spectrum is drawn from (400 to 4000)cm −1 . The FTIR peaks in the range of (490 to 600cm −1 ) correlates to Mn-O bending vibrations. The study of SEM images of synthesized Mn2O3 nanoparticles depicts the porous material. Interplanar distance is analyzed using TEM images and is found to be 0.21 nm for sample with 0.2 g fuel concentration. The study of UVDRS analysis gives the band gap ranging from 1.30 eV to 1.36 eV. EIS of the synthesized Mn2O3 nanoparticles gives the impedance in the range from 274.6 Ω to 323.8 Ω. The BET results confirm the sample Mn200 is of Type-II isotherm with the specific surface area about 2.4862 m 2 /g. The Mn2O3 nanoparticles prepared using 0.2 g fuel concentration exhibit improved Structural, Electrical and Electrochemical properties. Hence these nanoparticles may be used as electrode material in rechargeable batteries.